2010
DOI: 10.1007/s10956-010-9232-9
|View full text |Cite
|
Sign up to set email alerts
|

Simulated Sustainable Societies: Students’ Reflections on Creating Future Cities in Computer Games

Abstract: The empirical study, in this article, involved 42 students (ages 14 15), who used the urban simulation computer game SimCity 4 to create models of sustainable future cities. The aim was to explore in what ways the simulated ''real'' worlds provided by this game could be a potential facilitator for science learning contexts. The topic investigated is in what way interactions in this gaming environment, and reflections about these interactions, can form a context where the students deal with real world problems,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 28 publications
0
17
0
2
Order By: Relevance
“…To learn how to solve problems or to perform the cognitive process of problem solving (e.g. understanding, characterizing, representing, solving, reflecting, communicating and reasoning) using games was also the focus of some work like Moreno and Mayer (2000) and Nilsson and Jakobsson (2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…To learn how to solve problems or to perform the cognitive process of problem solving (e.g. understanding, characterizing, representing, solving, reflecting, communicating and reasoning) using games was also the focus of some work like Moreno and Mayer (2000) and Nilsson and Jakobsson (2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…and GeoNet reinforce basic geographic literacy (Brysch, Huynh, and Scholz 2012), others like SimCity and Minecraft challenge the player to think critically and creatively, and to solve problems with definite spatial dimensions. Action games have been found to enhance spatial cognition (Feng, Spence, and Pratt 2007), while CBGs and other simulation/strategy games encourage the player to exercise adaptive critical reasoning while continually critiquing different theories and strategies (Gaber 2007;Nilsson and Jakobsson 2011). The rules of the simulation, and the ways in which the game responds to user input therefore necessarily help shape players' perceptions of real-world systems and their geographies.…”
Section: Video Games As a Medium For Learningmentioning
confidence: 99%
“…They may also help to reinforce adaptive critical reasoning as students confront the many challenges of running a city (e.g., traffic, pollution, crime, natural disasters, negative cash flow, waste accumulation, citizen unrest). Other studies have demonstrated the efficacy of CBGs in reinforcing critical-thinking skills and introducing students to geographical patterns and processes (Adams 1998;Nilsson and Jakobsson 2011;Ting and Yang 2012;Kim and Shin forthcoming). At the university level, and particularly when used in planning education, however, the limitations and inaccuracies of these games limit their utility in understanding complex urban processes.…”
Section: Introductionmentioning
confidence: 99%
“…They can be used as a reflective and meta-cognitive tool, or an artefact, which helps to make teachers aware of the extent to which students can use and apply scientific concepts and theories in contextualised situations (Nilsson & Jakobsson, 2010). Along these lines, Barab and Dede (2007) argue that video games can offer contextualized learning situations in which students have the chance to broaden their understanding of science-related topics.…”
Section: Video Games In Formal Learning Contextsmentioning
confidence: 99%